Accomplishing an adaptive clinical trial for cancer: Valuation practices and care work across the laboratory and the clinic. (May 2020) - Swallow, Julia; Kerr, Anne; Chekar, Choon Key; Cunningham-Burley, Sarah
Abstract: A new generation of adaptive, multi-arm clinical trials has been developed in cancer research including those offering experimental treatments to patients based on the genomic analysis of their cancer. Depending on the molecular changes found in patients' cancer cells, it is anticipated that targeted and personalised therapies will be made available for those who have reached the end of standard treatment options, potentially extending survival time. Results from these trials are also expected to advance genomic knowledge for patients in the future. Drawing on data from a qualitative study of one such trial in the UK, comprising observations of out-patient clinic appointments, out-patient biopsy procedures, laboratory work, and interviews with practitioners, this paper explores how the clinical and research value of one such trial was accomplished in everyday practice by focussing on the work of clinical trials and laboratory staff across recruitment, laboratory analysis, and results management. In the face of numerous potential set-backs, disappointments and failure, we explore how practitioners worked to balance the need to meet established measures of value such as numbers of patients recruited into the trial, alongside cultivating the value of positive affects for patients by managing their expectations and emotions. This care work was performed primarily by practitioners whose roles have historically been devalued in healthcare practice and yet, as we show, were critical to this process. We conclude by arguing that as complex multi-arm adaptive trials become more commonplace, we need to attend to, and render visible, the dynamic and care-full valuation practices of backstage practitioners through which experimental biomedicine is accomplished, and in doing so show that care both achieves clinical and research value, and is also a series of practices and processes that tends to tissue, patients and staff in the context of ever-present possibility of failure. Highlights: Experimental genomic based trials are difficult to accomplish in practice. Valuation practices happen throughout recruitment and trial participation. Value was made via coordinative practices of care in the context of failure. Staff balance clinical and research value alongside expectations and emotions. Vital backstage practices of care were performed by devalued healthcare staff.